Pengaruh profitabilitas, inventory intensity, serta leverage akan agresivitas pajak dalam perusahaan manufaktur - Natasia Ayu Riskandari; Sholichah, Mu’minatus (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
The government raised its annual revenue target set for the tax sector, but many companies still view taxes as a burden that needs to be reduced. This condition causes companies to often look for ways to minimize their tax burden andtend to be tax aggressive. This study aims to determine the effect of profitability, inventory intensity, and leverage on tax aggressiveness. The research was conducted on manufacturing companies listed on the IDX for 2020-2021. This study used a purposive sampling method. Descriptive and quantitative statistics are used in this study. In this finding, it is explained that significant profitability hurts tax aggressiveness. Leverage has a significant positive effect on tax aggressiveness, and inventory intensity does not affect tax aggressiveness. Thus, companies with high profitability can fulfill their tax obligations. Companies with high leverage tend to be tax aggressive because companies use debt to manage expenses; this strategy ultimately leads to lower tax payments and retains more income